Rural transitions to net zero GHG emissions in Korea - Fuentes Hutfilter, Andrés (OECD Publishing, 2023)
This policy paper analyses the role of Korean rural regions in the country's transition to carbon neutrality by 2050, drawing on a conference organised by the OECD in collaboration with the Ministry of Land, Infrastructure, and Transport (MOLIT) of Korea. The report outlines the emissions profile of Korea's rural regions, compares them with other OECD countries and takes a deep dive on the three most emitting sectors: power generation, manufacturing, and transport. The paper then describes Korea's action plan to reach carbon neutrality. It discusses the just transition challenges in rural regions, highlighting employment risks and opportunities
Keywords: Urban, Rural and Regional Development; Korea, Democratic People's Republic of